Regional Policy of Germany during the Weimar Republic (1918-1933) in Soviet and post-Soviet Historiography - I. D. Popov (Научный диалог)
The article deals with the Soviet and post-Soviet historiography of the regional policy of Germany in the years of the Weimar Republic. It is noted that, despite an occasional appeal to this topic and often the overview and fragmentary nature of its research, over the past century, the main problems of regional development and the relations of the imperial center with the lands of 1918-1933 were identified and studied to varying degrees. It is shown that there are significant discrepancies in the historical assessments of the variability of the Sovietization of the regions during the November Revolution, the essence of Weimar federalism and the ways of its transformation, the position of the Reichsrat, the German-Prussian dualism, the character of the Ordnungszelle regime in Bavaria, the significance of imperial execution in Central Germany in 1923 and Prussia 1932, the nature of Rhine nationalism, the content of the policy of land unification. Each of these issues is discussed in the article. The main issue is the relationship of constitutional regulation of federal relations and their practical implementation. It is also concluded that there is practically no continuity between Soviet historians and scientists of the post-Soviet era in the assessments of the regional policy of Weimar Germany. In conclusion, the main gaps in the study of the regions of the Weimar Republic are presented, which can further form promising areas of research.